Find the residue of $$f(z)=\dfrac{z^3+2z+1}{(z-1)(z+3)}$$ on simple pole $z=1$.

If I using residue theorem, I have \begin{align} \underset{z=1} {\operatorname{Res}} f(z) = \lim\limits_{z\to 1} (z-1)\dfrac{z^3+2z+1}{(z-1)(z+3)}=\dfrac{1+2+1}{4}=1. \end{align}

If I using Laurent series method, I have \begin{align} f(z)&=\dfrac{z^3+2z+1}{(z-1)(z+3)}\\ &=(z-2)+\dfrac{9z-5}{(z-1)(z+3)}\\ &= -1+(z-1)+\dfrac{9(z+3)-32}{(z-1)(z+3)}\\ &= -1+(z-1)+\dfrac{9}{(z-1)}-\dfrac{32}{z-1}\cdot\dfrac{1}{z+3}\\ &= -1+(z-1)+\dfrac{9}{(z-1)}-\dfrac{32}{z-1}\cdot\dfrac{1}{z-1+4}\\ &= -1+(z-1)+\dfrac{9}{(z-1)}-\dfrac{32}{(z-1)^2}\cdot\dfrac{1}{1+\dfrac{4}{z-1}}\\ &= -1+(z-1)+\dfrac{9}{(z-1)}-\dfrac{32}{(z-1)^2}\sum\limits_{n=0}^{\infty} (-1)^n \left(\dfrac{4}{z-1}\right)^n\\ &= -1+(z-1)+\dfrac{9}{(z-1)}-\dfrac{32}{(z-1)^2}\sum\limits_{n=0}^{\infty} (-4)^n \left(z-1\right)^{-n}\\ &= -1+(z-1)+\dfrac{9}{(z-1)}+\sum\limits_{n=0}^{\infty} (-32)(-4)^n \left(z-1\right)^{-n-2}. \end{align} Now I have coefficient of $(z-1)^{-1}$ is $9$, so we can conclude \begin{align} \underset{z=1} {\operatorname{Res}} f(z) =9. \end{align} My question

When I using residue theorem and Laurent series method, why the result is distinct? What my mistake in my work?

  • 1
    $\begingroup$ I think you can't use Taylor expansion of $\frac{1}{1 +\frac{4}{z - 1}}$, because $|\frac{4}{z-1}| \to \infty$ at $1$, but you need $\frac{4}{z-1}$ to be close to zero to use it. $\endgroup$ – Nik Pronko Apr 28 '20 at 13:26

The "Laurent series method" had an incorrect conclusion going from the fourth to the fifth lines. There was a still an order $1$ term on the far right, it just still had to be pulled out.

We can calculate the Laurent series another way. From partial fraction decomposition we have that

$$\frac{4}{(z-1)(z+3)} = \frac{1}{z-1}-\frac{1}{z+3}$$

which means we can rewrite the function as

$$f(z) = \frac{z^3+2z+1}{4(z-1)} - \frac{z^3+2z+1}{4(z+3)}$$

This time the term on the far right has no singularity at $z=1$ so it will not contribute to the residue. We will only focus on the term on the left.

Next, shift the variables in the numerator to the desired center:

$$\frac{z^3+2z+1}{4(z-1)} = \frac{(z-1)^3+3(z-1)^2+5(z-1)+4}{4(z-1)}$$

$$ = \frac{1}{4}(z-1)^2+\frac{3}{4}(z-1) + \frac{5}{4} + \frac{1}{z-1}$$

which has a residue of $1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.